Comparison between adrenal venous sampling and computed tomography in the diagnosis of primary aldosteronism and in the guidance of adrenalectomy. Issue 39 (September 2016) - Zhu, Limin; Zhang, Ying; Zhang, Hua; Zhou, Wenlong; Shen, Zhoujun; Zheng, Fangfang; Tang, Xiaofeng; Tao, Bo; Zhang, Jin; Lu, Xiaohong; Xu, Jianzhong; Chu, Shaoli; et al.
Abstract : Abstract: In our series of patients with primary aldosteronism, we compared diagnostic concordance and clinical outcomes after adrenalectomy between adrenal venous sampling (AVS) and computed tomography (CT) imaging. Our retrospective analysis included 886 patients with primary aldosteronism diagnosed in our hospital between 2005 and 2014. Of them, 269 patients with CT unilateral adrenal disease were included in the analysis on the diagnostic concordance and 126 patients with follow-up data in the analysis on clinical outcomes after adrenalectomy. Hypertension was considered cured if systolic/diastolic blood pressure (BP) was controlled (<140/90 mm Hg) without medication and improved if BP was controlled with a reduced number of antihypertensive drugs. In 269 patients with CT unilateral adrenal disease, the overall concordance rate between AVS and CT was 50.5% for lateralization on the same side. The concordance rate decreased with increasing age, with highest rate of 61% in patients aged <30 years (n = 16). In 126 patients with follow-up data after adrenalectomy, the AVS- (n = 96) and CT-guided patients (n = 30) had similar characteristics before adrenalectomy. After andrenalectomy, the AVS-guided patients had a significantly higher serum potassium concentration (4.3 ± 0.3 vs 4.0 ± 0.5 mmol/L, P = 0.04) and rate of cured and improved hypertension (98% vs 87%, P = 0.03). The AVS-guided patients (n = 50) had slightly higher cured rate than the CT-guided patients (n = 11) in those older than 50 years (26.0% vs 18.2%, P = 0.72). The age below which the cured rate in the CT-guided patients was 100% was 30 years. AVS guidance had moderate concordance with CT and slightly improved clinical outcomes after adrenalectomy. The age below which CT unilateralization achieved 100% cured rate was approximately 30 years.